Analisys of the Influence of Total Labor and Total Raw Material Inventory toward Furniture Production Volume at PT Harrison & Gil Java Semaran - Alfiatin - Dwijayanti; Suryadi - Poerbo; Suwardi - Suwardi (Admisi dan Bisnis, 2019)
This study aims to analyze the influence of total labor and total raw material inventory toward furniture production volume at PT Harrison & Gil Java Semarang. The data used in this research is secondary data which are the report of total labor, total raw material inventory, and furniture production volume in 2016-2018 at PT Harrison & Gil Java Semarang. Data collection method that used in this research are observation and interview. The analysis technique used are Classical Assumption Test, Multiple Linear Regression, and Goodness of Fit test. Based on the research that had been done, the F test shows that Total Labor and Total Raw Material Inventory had a significant effect to Furniture Production Volume of PT Harrison & Gil Java Semarang simultaneously. Meanwhile the result in t test shows that only the Total Raw Material Inventory that had a significant effect on Furniture Production Volume with the t significance value less than the α significance value (0,000 < 0,05). Based on the adjusted R2 vaue about 0,875 means that 87,5% change in the Furniture Production Volume of PT Harrison & Gil Java can be explained by the two independent variables that were Total Labor and Total Raw Material Inventory, while the rest of 12,5% was explained by other variables outside the model